Externalized Borders, Internalized Control: The Politics of Detention in Indonesia-Australia Migration Governance - Mohammad Nashiir; Atin Prabandari (Sospol, 2026)
This journal article analyzes the internalization of Australian border controls within Indonesia's immigration detention governance. The primary research focus is the active agency of domestic authorities, which has been largely overlooked in existing literature. Utilizing a qualitative method with a case study of Rudenim Tanjungpinang, a facility occupying a crucial migration corridor between both nations, this study uncovers the strategies of local actors exploiting external funding for national interests. The conceptual framework integrates border externalization, strategic non-regulation, and migrant rentierism to dissect data from journals, books, policy documents, and official reports. Findings demonstrate that through regulatory ambiguity, Indonesian officials successfully assert territorial sovereignty while extracting political and financial benefits from Australia. Consequently, Rudenim Tanjungpinang operates as a hybrid control apparatus, shifting external containment into domestic management. Beyond these mutual state benefits, asylum seekers endure the tragic consequence of being trapped in prolonged limbo. This inquiry underscores that transit states are proactive strategic agents within the global political economy of migration. Due to specific facility data limitations, the depth of analysis is carefully situated within broader national and bilateral migration patterns.